2019
DOI: 10.1111/jcmm.14844
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of MTHFD2 inhibits NSCLC progression by suppressing cycle‐related genes

Abstract: Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) is a bifunctional enzyme located in the mitochondria. It has been reported to be overexpressed in several malignancies. However, the relationship between the expression of MTHFD2 and non-small cell lung cancer (NSCLC) remains largely unknown. In this study, we found that MTHFD2 was significantly overexpressed in NSCLC tissues and cell lines. Knockdown of MTHFD2 resulted in reduced cell growth and tumorigenicity in vitro and in vivo. Besides, the mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
8
33
0
Order By: Relevance
“…MTHFD2 overexpression is associated with poor prognosis and tumor metastasis in HCC and breast cancer [24,25]. In vitro and in vivo experiments of NSCLC indicated that knockdown of MTHFD2 can reduce cell growth and tumorigenicity [26]. Kawai et al [27] reported that DS18561882, an MTHFD2 inhibitor, has a strong antitumor effect on mouse xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…MTHFD2 overexpression is associated with poor prognosis and tumor metastasis in HCC and breast cancer [24,25]. In vitro and in vivo experiments of NSCLC indicated that knockdown of MTHFD2 can reduce cell growth and tumorigenicity [26]. Kawai et al [27] reported that DS18561882, an MTHFD2 inhibitor, has a strong antitumor effect on mouse xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that suppression of MTHFD2 inhibits methylation reactions (7), decreases protein synthesis (9) and disrupts redox homeostasis (6,10), which may ultimately result in significant changes in cellular metabolic phenotype. Because MTHFD2 expression was reported as a key participant in the metabolic reprogramming in tumors (7) and a predictive factor of poor prognosis in patients with various types of cancer (8,(11)(12)(13), including breast cancer (14), MTHFD2 has received increased attention recently and might be considered as a potential anticancer target. Numerous studies have also demonstrated a strong association between tumor cell phenotype and MTHFD2 expression status (13,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…MTHFD2 was found highly expressed in colorectal cancer (CRC) cells, and silence of MTHFD2 expression inhibited the proliferation, weakened the migration ability and promoted the apoptosis of CRC cells [17]. MTHFD2 was also significantly over-expressed in non-small cell lung cancer (NSCLC) tissues, and knockdown of MTHFD2 resulted in reduction of tumor cell growth and tumorigenicity [18]. In addition, MTHFD2 over-expression was associated with cell proliferation and vimentin-modulated migration and invasion in renal cell carcinoma (RCC) [19].…”
Section: Discussionmentioning
confidence: 99%